PROBLEMS AND SOLUTIONS OF GLOBALIZATION, LANGUAGE POLICY, AND LINGUISTIC IDENTITY IN MODERN LINGUISTICS - XamidjonovaMoxigul Ortiqboyqizi; Alikberova Kamila Adkhamovna (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Problems and Solutions of Globalization, Language Policy, and Linguistic Identity in Modern Linguistics Abstract. Globalization has significantly influenced language development, language policy, and linguistic identity in modern societies. The growing dominance of international languages, particularly English, has facilitated global communication but also created challenges for minority languages and cultural identity. This study examines the major problems related to globalization and linguistic diversity, focusing on language shift, cultural identity loss, and unequal language policies. The paper also discusses possible solutions such as multilingual education, balanced language planning, and language preservation programs. The findings emphasize the importance of protecting linguistic diversity while benefiting from global communication.